Elektrolit pepejal polimer 49% poli (metil metakrilat) cangkukan getah asli - litium tetrafluoroborat - Azizan Ahmad,; Pow, Chee Lien; Mohd Sukor Su’aAit, (Universiti Kebangsaan Malaysia, 2010)
The potential of 49% poly(methyl methacrylate) grafted natural rubber (MG49) as a solid polymer electrolyte film for application in electrochemical device system has been investigated. The MG49 films with LiBF4 as a doping salt were prepared by solution casting technique. The ionic conductivity investigated by electrochemical impedance spectroscopy showed the optimum ionic conductivity was given by 25 wt% of LiBF4 salt loading with ionic conductivity value, 1.49×10-9 S.cm-1 at room temperature. The observation on structural and morphology studies have been done by X-ray diffraction and scanning electron microscopy. Results showed that complexation and crystallization occurred in polymer electrolyte system. This gave low electrical conductivity value eventhough the addition of LiBF4 salt has reached the optimum level.